2015
DOI: 10.3151/jact.13.82
|View full text |Cite
|
Sign up to set email alerts
|

Flexural and Interface Behaviors of Reinforced Concrete/Ultra-high Toughness Cementitious Composite (RC/UHTCC) Beams

Abstract: This paper presents an experimental investigation on the response of reinforced concrete (RC) beams with the use of ultra-high toughness cementitious composite (UHTCC) in the tension zone. Two parameters, the longitudinal reinforcement ratio and the depth of UHTCC layer, were varied. The failure mechanism, flexural behavior, interface performance, and cracking pattern were compared between RC and RC/UHTCC beams as well as between RC/UHTCC beams with different depths of the UHTCC layer. The experimental results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…At the time of casting the top layer, the bottom layer was strong enough to support the top layer matrix, i.e. deformation of the layer interface was avoided; while the initial setting of the bottom layer matrix had not been reached [37,51], resulting in a strong interfacial bond. This casting method, on the one hand, induces to a sufficient layer bond strength; on the other hand, the existence of the layer interface can act as a source of micro-cracking, which consumes more fracture energy during the cracking process (this will be further explained in Section 4.3).…”
Section: Mixing and Casting Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of casting the top layer, the bottom layer was strong enough to support the top layer matrix, i.e. deformation of the layer interface was avoided; while the initial setting of the bottom layer matrix had not been reached [37,51], resulting in a strong interfacial bond. This casting method, on the one hand, induces to a sufficient layer bond strength; on the other hand, the existence of the layer interface can act as a source of micro-cracking, which consumes more fracture energy during the cracking process (this will be further explained in Section 4.3).…”
Section: Mixing and Casting Proceduresmentioning
confidence: 99%
“…the thickness of the layer is randomly chosen and the influences of the layer thickness are not considered. Xu et al [36] and Hou et al [37] presented theoretical and experimental investigations on steel-bar reinforced concrete with an ultra-high flexural energy concrete (UHTCC) layer, in which effects of the reinforcement ratio and the layer thickness were discussed. It showed that the interface cracking and ultimate bonding strengths are related to the reinforcement ratio and UHTCC layer thickness.…”
Section: Introductionmentioning
confidence: 99%
“…22 The layer depth and the reinforcement ratio both have major effects on the bonding strength between the concrete layers. 23 The flexural strength of the two-layered beam increased nonlinearly with increasing layer thickness. 24,25 The compressive strength of a layered section is close to that of the weakest material in the section, and the layered section stiffness is the average of the values of the two materials used.…”
Section: Introductionmentioning
confidence: 99%
“…Under the service load condition, it was found that the ECC layer prevented the migration of aggressive substances into the concrete. Further, experimental studies are reported on the performance of layered composite beams subjected to flexural loads [24][25][26]. The HPFRCC layer was provided at both the top and bottom faces of the beam, and their study concluded that the layer of HPFRCC at the bottom of the beam section was more effective than using it on the top of the section [24].…”
Section: Introductionmentioning
confidence: 99%